The judicialisation of discrimination in the Indonesian constitutional court - Ibrahim, Mohammad (SAGE Publications Ltd, 2022)
Following the post-Soeharto constitutional reform from 1999 to 2002, the Indonesian Constitutional Court was established with powers, inter alia, to review the constitutionality of national legislation. The constitutional amendments also incorporated a constitutional Bill of Rights, which includes the right to be free from discrimination on any ground and the right to protection against discrimination under Article 28I(2) and the right to equality before the law under Article 28D(1). However, the Constitution does not specify an enumerated list of grounds against which discrimination is prohibited. This article examines a body of constitutional jurisprudence in Indonesia, an Asian civil law country with no formal system of precedent. It seeks to determine the extent to which the Indonesian Constitutional Court has protected the citizens' fundamental rights of equality and against discrimination. Through describing and analysing three court decisions on the principles of equality and non-discrimination, this article argues that the Indonesian Constitutional Court, in its early years of operation, took these principles seriously. Nevertheless, in its later decisions, the Court departed, albeit not explicitly, from its earlier ruling by relying on ‘the belief in One God’ and ‘the religious values consideration’ under Articles 29(1) and 28J of the Constitution to restrict the fundamental rights of equality and non-discrimination. Consequently, the Court has unjustifiably held that discrimination is not prohibited insofar as it is in accord with religious orthodoxy.